Endoscopic Procedures in the Treatment of Ureteroenteric Anastomotic Strictures: A Systematic Review and Meta-Analysis - Lu, Xun; Wang, Yiduo; Chen, Qi; Xia, Di; Zhang, Hanyu; Chen, Ming (Frontiers in Surgery, 2021)
Abstract Objective: To evaluate the safety and efficacy of endoscopic procedures for ureteroenteric anastomotic strictures (UES) after radical cystectomy and urinary diversion. Methods: We performed a meta-analysis of relevant articles through March 2020 using PubMed, Embase, and Cochrane Central Register to assess the efficacy of endoscopic procedures in UES. The main endpoints were success rate and complications, and we also compared the efficacy of different methods and stricture length and side in UES. Cochrane Collaboration’s Revman version 5.3 and Stata version 15.1 software were used for statistical analysis. Results: A total of 18 retrospective studies with 697 patients were included. The median follow-up ranges from 12 months to 62.5 months. Patients treated with endoscopic procedures had an overall success rate of 46%. The pooled rate of Clavien–Dindo ≥3 complications was 3.8% among included studies. Laser vaporization and stent insertion (48% and 47%) had a relatively high success rate than balloon dilatation (35%). In subgroup analysis, the success rate of endoscopic procedures for ≤1cm strictures was significantly higher than that for >1 cm ones [OR, 8.65; 95% Cl, 3.53 to 21.21; P < 0.00001]. In addition, the success rate in cases with strictures of right side was relatively higher than that in cases with strictures of left side [OR, 1.72; 95% Cl, 1.05 to 2.81; P = 0.03]. Conclusion: Our pooled studies showed that endoscopic operation has a high success rate and low incidence of perioperative complications in the treatment of UES, especially with length ≤1 cm and right side. Although there is still no consensus on endoscopic technique for UES regarding balloon dilatation, stent insertion and laser vaporization, we deem endoscopic management is a safety and effective approach for UES.